2021
DOI: 10.1097/gox.0000000000003675
|View full text |Cite
|
Sign up to set email alerts
|

Joint Treatment of De Novo Umbilical Endometriosis with Plastic Surgery and Minimally Invasive Gynecologic Surgery

Abstract: Related Digital Media are available in the full-text version of the article on www.PRSGlobalOpen.com.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…In cases of umbilical endometriosis, resection must be followed with umbilical reconstruction. Hamouie et al 12 reported a case of chronic abdominal wall endometriosis with invasion of the umbilicus and surrounding cutaneous tissue, in which they performed a novel four-flap umbilicoplasty technique to reconstruct the umbilicus as well as to add support to the inferior abdominal wall repair. Takaya et al 34 described a case of cutaneous endometriosis secondary to a cesarean section, in which they performed resection of the endometrial tissue and placement of synthetic mesh.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In cases of umbilical endometriosis, resection must be followed with umbilical reconstruction. Hamouie et al 12 reported a case of chronic abdominal wall endometriosis with invasion of the umbilicus and surrounding cutaneous tissue, in which they performed a novel four-flap umbilicoplasty technique to reconstruct the umbilicus as well as to add support to the inferior abdominal wall repair. Takaya et al 34 described a case of cutaneous endometriosis secondary to a cesarean section, in which they performed resection of the endometrial tissue and placement of synthetic mesh.…”
Section: Discussionmentioning
confidence: 99%
“…Perry et al 11 reported a case of an abdominoplasty for a patient with a history of polycystic ovarian syndrome and hypothyroidism, in which the patient had no complaints of local pain or a palpable abdominal mass. Hamouie et al 12 described a notable case of primary…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations